Effects of N-methyl-N-nitrosourea on seed germination of Stevia rebaudiana - Ahmad, Lyena Watty Zuraine; Zainuddin, Zarina; Osman, Mohamad; Mohamad, Azhar; Jaafar Sidik, Norrizah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Stevia rebaudiana is a unique plant that contains non-caloric natural sweetener and has gained much interest among Malaysians. In this study, the effect of different concentrations of N‑methyl-N-nitrosourea (MNU) was assessed in inducing mutation in Stevia seeds to produce genetic variations, which is valuable for crop improvement. Stevia seeds were soaked in six concentrations of MNU (0.0, 0.13, 0.25, 0.38, 0.50, and 1.00 mM) for four different durations (15, 30, 45, and 60 min) at room temperature. As a result, application of MNU reduced the germination percentage and germination rate of Stevia seeds as compared to the control group. Prolonged exposure to the highest concentration of MNU recorded the lowest percentage of germination (2.5 ± 1.4%) and the lowest germination rate (0.21 ± 0.16). Tricots were observed among seedlings treated with 0.13, 0.38 and 1.0 mM of MNU for 30 min. Presence of seedlings with albino colour proved the mutagenic effect of MNU on Stevia genome. Based on the percentage of seedlings with chlorophyll mutation, the most effective and efficient mutagenic treatment to induce mutation was 60 min in 0.25 mM of MNU.